USAGE OF NUKLEX IN THERAPY OF PATIENTS WITH HEPATITIS C - Dyky, B.M.; Kondryn, O.Ye.; Pryshliak, O.Ya.; Tkaschuk, Z.Yu. (Інфекційні хвороби, 2013)
Usage of Nuklex for treatment of hepatitis C is accompanied by a rapid disappearance of the main clinical symptoms, improvement of health in the patients, supports normalization of cytolytic liver function in patients with minimal or moderate activity hepatitis. Based on the obtained data, it can be considered the isolate usage of Nuklex as the only antiviral drug for hepatitis C patients with low initial viral load HCV (<800,000 IU/ml) in a daily dose of 1.5 g. It is rather prospective to continue to study the efficiency of Nuklex in patients with hepatitis C with an initial high viral load HCV (>800,000 IU/ml) in complex therapy with other antiviral drugs